An "oxhorn"-shaped V–Y advancement flap unilaterally pedicled on a nasal superficial musculoaponeurotic system for nasal reconstruction. Issue 11 (November 2015) - Xu, Miao; Yang, Chao; Wang, Wen-Jin; Bi, Hong-Da; Xing, Xin
Summary: Background: Laterally based nasalis myocutaneous flaps pedicled on the superior nasal superficial musculoaponeurotic system (SMAS), which contains the bilateral dorsal nasal arteries, have not been utilized for the reconstruction of nasal defects. Methods: According to the location and size of the nasal defects, a V–Y advancement nasalis myocutaneous flap was designed along the proximal alar groove and nasolabial fold. The flap was superficially elevated from the perichondrium, and the nasal SMAS above the flap was dissected as the unilateral pedicle. After the flap was rotated and advanced to the defect, the secondary defect was primarily closed. Results: A total of 20 cases of nasal defects, including six cases of nasal dorsum, five cases of nasal tip, four cases of nasal tip-alar junctions and five cases of nasal tip-dorsum junctions, were reconstructed using this method. The defect size ranged from 0.8 × 0.8 cm to 2 × 1.8 cm. All of the flaps survived with satisfactory aesthetics and function. All of the patients were postoperatively followed up for 6–12 months. Conclusion: Application of the V–Y advancement nasalis myocutaneous flaps pedicled on a nasal SMAS is appropriate for the reconstruction of small to medium sized nasal tips and peri-tip defects, and it can achieve satisfactory results due to its simple design, convenient transfer, reliable blood supply and concealed incision.